Kegiatan Eksplorasi dalam Proses Perilaku Pencarian Informasi Seniman Mural di Institut Kesenian Jakarta - Khairunnisa Nastiti Amany; Agus Rusmana; Rully Khairul Anwar (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
This study describe about one of the activities in information seeking behaviour model proposed by Carol Kuhlthau. This study used a qualitative exploratory with a qualitative approach. In this study, the data accumulation was done by interview, observation and by literature study. In this case, author chose exploration activities therein describes the use of resources and constraints experienced during the seeking information. The result showed that the mural artist use resources from the internet, combining print and the electronic media, as well as using life experience and observation of the environment. The next is, constraints experienced by mural artist. They mention that the constraints of the internet connection, limited information is discovered, and internal factors of the self that become obstacles in search of the information